Three cases of partial trisomy 7q owing to rare structural rearrangements of chromosome 7. Issue 2 (February 1990) - Romain, D R; Cairney, H; Stewart, D; Columbano-Green, L M; Garry, M; Parslow, M I; Parfitt, R; Smythe, R H; Chapman, C J
Abstract : Three cases of partial trisomy 7q are described. One case had duplication of region 7q22.1----q31.2 owing to a de novo direct intra-arm intrachromosomal duplication. The other two cases, first cousins, were trisomic for 7q34----qter, resulting from recombination within the inserted segment of a dir ins(7;17)(q34;q23.1q25.3)mat. All three cases had a number of the already recorded manifestations of partial trisomy 7q, namely strabismus, low set ears, depressed nasal bridge, small nose, hypotonia, and mental retardation.